APLIKASI BIOCHAR SEKAM PADI TERHADAP PERTUMBUHAN DAN HASIL TANANAMAN BAYAM MERAH (Amaranths gangenticus) - Putu Lasmi Yuliyanti Sapanca; Putu Eka Pasmidi Ariati; Adrianus Nurdin Ndatu (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
Spinach plant Besides being used as an ornamental plant, it is also a vegetable plant that contains a lot of protein. The production of red spinach has increased, but has not been able to meet market needs. Therefore, research on red spinach plants needs to be carried out with the aim of: 1) Knowing the effect of giving rice husk biochar on the growth and yield of red spinach plants. 2) Knowing the best dose of rice husk biochar on the growth and yield of red spinach plants. This study used a Randomized Block Design (RAK) method with six treatments, namely treatment without biochar (P0), treatment with biochar 25 / 10 kg of soil (P1), treatment with biochar 50 g / 10 kg of soil (P2), treatment with biochar 75 g / 10 kg of soil (P3), treatment of biochar 100 g/10 soil (P4), and treatment of biochar 125 g/10 kg of soil (P5) each treatment was repeated four times so that the total of all treatments became 24. In testing the effect of the dose of rice husk biochar on red spinach plant, application of rice husk biochar 125 g/10 kg of soil gave the best growth results for all observed parameters, namely: plant height (cm), number of leaves (strands), leaf area (cm), total plant fresh weight ( g), and total plant oven dry weight (g).